Investigation of the Presence of Women in Political Positions in the Kurdistan Regional Government - Dadfar, Dr. Arman Esmaeil Dadfar. (Sulaimani Journal for Humanities, 2026)
Public participation of the people in political affairs, which is itself a result of their desire to seek participation in the political system, is one of the results and achievements of the advanced stages of democracy. Participation can be considered one of the success criteria of comprehensive development. The snake brought women as half of Human resources in human societies, which are one of the most important sources of development, play an important role in the development of human societies. So far, men have not wanted or have not been able to support the interests of women sufficiently. As a result, women's participation in all social activities, such as the field of politics, is necessary, in such a way that it can be said that the minority role of women in political affairs causes democracy to remain sterile in society. The Human Development Report of the United Nations Organization, which ranks the various countries of the world in terms of action to prepare in its latest report in the year 2022, identifies the human development report of the actions of the countries under study. Regarding the level of adherence and importance of the governments in the show It is Although the current study about the relative position of women will focus on economic and political variables, this does not mean that the position of women in any society can be determined only by referring to political and economic measures. It is explained this issue is also important that the position and rank of the desired woman is not static and dynamic and in addition to the fact that due to the time and place conditions are changing and the position and position of the woman should always be among the conditions that shape the economy and politics. New The world will be re-evaluated. The basis and conditions against which the relative position of women is measured are in constant instability and, under the influence of technological advances, existing relations between the government and the market, education, upbringing, and change, the attitude is extremely unstable. It will be will take (Johnston and others 2004, 293)